1984
DOI: 10.1115/1.3239648
|View full text |Cite
|
Sign up to set email alerts
|

Water-Ethanol-Gasoline Blends—Physical Properties, Power, and Pollution Characteristics

Abstract: Factors relevant to the utilization of nonanhydrous ethanol as a blending component with gasoline for use in current on-the-road spark ignition engines are investigated. Miscibility limits are determined and key physical properties important for proper engine operation are measured. Dynamometer tests on an unmodified production engine with hydrated ethanol-gasoline blends containing varying percentages of water show potential for increased thermal efficiency and reduced oxides of nitrogen emissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Cases 5 and 6 (which have water injection) indicate relative reductions of 10.4% and 25.3% in NOx emissions, respectively. The ethanol content itself demonstrated a decrease in NOx emission; this observation is consistent with some of the previous studies [10][11][12][13][14] and is primarily due to high heat of vaporization of ethanol compared to gasoline, which decreases the charge temperature [15].…”
Section: Combustion E Ciencysupporting
confidence: 90%
See 1 more Smart Citation
“…Cases 5 and 6 (which have water injection) indicate relative reductions of 10.4% and 25.3% in NOx emissions, respectively. The ethanol content itself demonstrated a decrease in NOx emission; this observation is consistent with some of the previous studies [10][11][12][13][14] and is primarily due to high heat of vaporization of ethanol compared to gasoline, which decreases the charge temperature [15].…”
Section: Combustion E Ciencysupporting
confidence: 90%
“…This was attributed to a faster ame speed, which produced a higher peak pressure and, therefore, a higher peak temperature in the combustion process. However, there are some discrepancies in the literature on the e ect of ethanol on NOx emissions of SI engines [10], and there are a number of other studies that have demonstrated a reduction in NOx emissions using ethanol gasoline blends [11][12][13][14]. This has been attributed to high heat of vaporization of ethanol compared to gasoline, which decreases the charge temperature and reduces thermal NOx formation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Das et al [48] investigated the influence of water addition on the combustion rate of H 2 /CO-air mixtures, and found that the combustion rate increased because the improvement in chain reactions due to water addition was much more pronounced than the negative thermal effect for low percentages of water addition. Dryer [49] and Rajan [50] also explained the improved combustion rate as a result of the catalytic activity of water vapor due to increased OH radicals. In addition, the water addition reduced combustion temperature and lowered the combustion rate.…”
Section: Effect Of Water Additive On Performance Combustion and Emismentioning
confidence: 98%
“…In addition, the lower particle concentration obtained with hydrous ethanol and anhydrous ethanol blends in comparison to gasoline due to the higher hydrogen to carbon ratio, higher volatility, higher percentage of oxygen content in the fuel, and no sulfur and aromatics in ethanol also favored the repression of PM formation inside the cylinder [69]. Another mechanism for the remarked decrease is the oxidation of PM emission by OH radicals from ethanol [70], and by H, O, and OH radicals from water dissociation [13,71,72]. According to chemical kinetics model results published by Zhang et al [59], the addition of water in fuel encourages the formation of free radicals O, H, and OH, which encourages the oxidation of emissions.…”
Section: Pm Emission Characteristicsmentioning
confidence: 99%